2005
DOI: 10.1016/j.physletb.2005.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dynamics of massive particles in a non-commutative two-sheeted space–time

Abstract: We study a formal extension of the Dirac equation in the framework of a non-commutative twosheeted space-time. It is shown that this approach naturally extends the classical Dirac theory by doubling the number of fermionic states, which can then be identified as matter and hidden-matter states. Our model exhibit several interesting features that could have observational consequences. Among them, we predict a small electromagnetic coupling between matter and hidden matter universes which should lead to matter/h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 20 publications
(107 citation statements)
references
References 13 publications
5
101
0
1
Order By: Relevance
“…In previous works [15][16][17][18][19], two of the present authors (Sarrazin and Petit) have shown that for a bulk containing at least two parallel 3-branes hidden to each other, matter swapping between these two worlds should occur. The particle must be massive, can be electrically charged 1 or not, but must be endowed with a magnetic moment.…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations
“…In previous works [15][16][17][18][19], two of the present authors (Sarrazin and Petit) have shown that for a bulk containing at least two parallel 3-branes hidden to each other, matter swapping between these two worlds should occur. The particle must be massive, can be electrically charged 1 or not, but must be endowed with a magnetic moment.…”
Section: Introductionmentioning
confidence: 56%
“…From Ref. [16], we get g < 3 × 10 10 m −1 from the millicharge constraint ε < 4.1 × 10 −5 [38]. Even with more recent and stringent constraints [13,39], we get g < 9 × 10 7 m −1 from ε < 3 × 10 −10 (see Berezhiani and Lepidi in Ref.…”
Section: Constraints On G and ηmentioning
confidence: 91%
See 2 more Smart Citations
“…(2) [31]. The incorporation of the electromagnetic field in the model can be done quite easily [30][31][32]. The usual U(1) gauge field must be substituted by an extended U(1) U(1) gauge relevant for the discrete Z 2 structure of the universe.…”
Section: Physical and Mathematical Frameworkmentioning
confidence: 99%